Pengembangan Modulus Elastisitas Campuran Aspal, Standar Load Group Dan Angka Ekivalen Pada Manual Desain Perkerasan Jalan 2017 - Yahya, Muhammad Alif; Nurdin, Abd Rahim; Yunianti, Nurhadijah (Program Studi Teknik Sipil Universitas Bosowa, 2025)
The accuracy of predicting the elastic modulus of asphalt mixtures is crucial for analyzing pavement structure performance. This prediction impacts pavement responses, including tensile strain below the surface layer and compressive strain below the subgrade. Calculating equivalent standard axle loads (ESALs), specifically ESAL 4 and ESAL 5, is essential for determining pavement thickness. To ensure that flexible pavement provides safe and comfortable service, it is important to design the pavement structure to meet the planned service life. The pavement thickness was calculated using the 2017 manual pavement design method, followed by analysis with the Asphalt Institute method to predict load repetitions leading to potential road damage, such as fatigue cracking and permanent deformation. This research, a quantitative descriptive study with a case study approach, was conducted on HM. Yasin Limpo Road in Gowa Regency. The results indicated pavement layer thicknesses of 4 cm for AC-WC, 6 cm for AC-BC, 16 cm for AC-Base, and 20 cm for Class A subbase. The tensile strain value was 0.0001932 kilopascals, with load repetitions amounting to 24,324,108 ESALs, while the compressive strain was 0.0003511 kilopascals, with load repetitions of 39,924,439 ESALs.